2022
DOI: 10.1186/s11658-022-00368-y
|View full text |Cite
|
Sign up to set email alerts
|

The current landscape of microRNAs (miRNAs) in bacterial pneumonia: opportunities and challenges

Abstract: MicroRNAs (miRNAs), which were initially discovered in Caenorhabditis elegans, can regulate gene expression by recognizing cognate sequences and interfering with the transcriptional or translational machinery. The application of bioinformatics tools for structural analysis and target prediction has largely driven the investigation of certain miRNAs. Notably, it has been found that certain miRNAs which are widely involved in the inflammatory response and immune regulation are closely associated with the occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 151 publications
0
11
0
Order By: Relevance
“…Multiple studies indicate that miRNAs have the potential to mediate inflammatory response and immune regulation in pneumonia development. 27 Considerable data have revealed that miR-370-3p affects pneumonia occurrence through various molecular pathways. For example, miR-370-3p combined with the long noncoding RNA KCNQ1OT1/ miR-370-3p/FOXM1 axis to ameliorate lipopolysaccharide-induced WI-38 cell injury, as revealed by a cellular model of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies indicate that miRNAs have the potential to mediate inflammatory response and immune regulation in pneumonia development. 27 Considerable data have revealed that miR-370-3p affects pneumonia occurrence through various molecular pathways. For example, miR-370-3p combined with the long noncoding RNA KCNQ1OT1/ miR-370-3p/FOXM1 axis to ameliorate lipopolysaccharide-induced WI-38 cell injury, as revealed by a cellular model of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 6 shows that mir-221 also inhibits BECN1. The increase of the expression of this miRNA has been linked with bacterial infection of L. pneumophila as well [61]. Although a direct connection between mir-221 and xenophagy has not been described, their potential connection could indicate that this microRNA plays a role in pathogen defense.…”
Section: Applicationmentioning
confidence: 99%
“…5). 145 Strong evidence reveals that miRNA will be a potential nucleic acid therapy gene drug for bacterial treatment, in particular those derived from herbal medicine named exogenous small RNAs.…”
Section: Application Of Nucleic Acid Therapymentioning
confidence: 99%